Effects of socio-cultural mathematics instruction on student interest and achievement - Sabo-o, Mae Arante (2006)
This study sought to determine the effects of using socio-cultural mathematics, integrating Seventh-day Adventist Bible stories and religious events in the lesson, on students' mathematical achievement and interest in Mathematics. Two intact first year classes of 450 students each from Lipa Adventist Academy in Batangas were used. They were taught for one hour each daily for three months using ten lesson plans for each class. The Mathematics Achievement Test, Interest in Mathematics Scale, and Survey Questionnaires for the interview were used to gather data. It was found that students exposed to socio-cultural mathematics did not have significantly higher achievement score nor interest than those not exposed to it. Nevertheless, socio-cultural mathematics instruction promoted a peaceful and conducive environment for learning.
"March 2006."
Thesis (M.A. Education : Mathematics Education)--University of the Philippines, Diliman.
Keywords: Seventh-Day Adventists -- Education; Mathematics -- Study and teaching (Secondary) -- Philippines -- Lipa City (Batangas).; High school freshmen -- Philippines -- Lipa City (Batangas).